The Effect of Anti-Doping Education on Volleyball Team Athletes' Knowledge and Attitudes - Daffaa Ikhsan; Irfan Marhandika; Rakha Syamsudin; Muhammad Arief Setiawan; A. Ine Aprilia Damai; Aprilia Wulan Utari (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
Doping is a serious problem in the world of sports that can undermine sportsmanship, health, and the integrity of athletes. College athletes’ limited understanding of banned substances and the lack of anti-doping education increase the risk of doping violations, whether intentional or unintentional. This study aims to determine the effect of anti-doping education on the knowledge and attitudes of Unsika volleyball club athletes. The study used a quantitative approach with a quasi-experimental method through a One-Group Pretest-Posttest Design. The study sample consisted of 30 athletes selected using total sampling. Data collection was conducted using a knowledge test and an attitude questionnaire, followed by analysis using the Shapiro-Wilk normality test and the Paired Sample T-Test. The results showed an increase in the mean score from 58.70 in the pretest to 82.67 in the posttest. The results of the Paired Sample T-Test showed a significance value of 0.000 < 0.05, indicating a significant effect of anti-doping education on athletes’ knowledge and attitudes. Thus, anti-doping education has proven effective in enhancing athletes’ understanding and fostering positive attitudes toward the importance of sportsmanship and doping-free sports.